Analisis Penerapan Peraturan Menteri Kelautan dan Perikanan RI No. 2/Permen-KP/2015 tentang Larangan Penggunaan Alat Penangkapan Ikan Pukat Hela (Trawls) dan Pukat Tarik (Seine Nets) di Wilayah Pengelolaan Perikanan Negara RI Sebagai Upaya Perlindungan Te - Bayu Putra Samara; Syafruddin Kalo; Madiasa Ablisar; Edy Ikhsan (Universitas Sumatera Utara, 2019)
Abstract : Provisions regarding fishing gear for trawlers around the Indonesian Ministry of Maritime Affairs and Fisheries No. 2 / PERMEN-KP / 2015 concerning the Prohibition of the Use of Fishing Tools for Trawlers and Trawlers (Seine Nets) in the Areas Addressing the Fisheries of the Republic of Indonesia. The use of fishing gear issued is fishing gear for trawlers and trawlers. On September 10, 2016, at around 17:00 West Indonesia Time, there was a burning of KM. Star of the Sea and KM. Kurnia Jaya Welcome to the boat in Asahan Regency and Tanjung Balai City, which is carried out by traditional fishing communities that use nets. At the time of this repair, there was also a persecution by the community of securing a motor boat named KM. Star of the Sea and KM. Kurnia Jaya Selamat, who prevented the burning carried out by the fishing community. The reason for burning is done because the fishing gear that uses the trawl (Trawl) (Trawl Tiger) is not environmentally friendly and the habitat of fish roasted / damages the preservation of the marine environment. The results of the fishing community interviews with fishermen who use puput netting tools explain the causes of the boat ride and the persecution in Tanjung Balai - Asahan related to traditional fishing communities in Asahan Regency and Tanjung Balai City asking for help and support for the operation of motorboats / engines using trawlers